Anterior maxillary osteotomy: A technical note for superior repositioning: A bird wing segment - V Sadesh Kannan; A Saneem Ahamed; G R Sathyanarayanan; K Velaven; E Elavarasi; C Danavel (Wolters Kluwer Medknow Publications, 2014)
Aim: The aim of this study is to evaluate the efficacy of a single piece bird wing osteotectomy segment during anterior maxillary osteotomy (AMO) markedly reduces the duration of the surgery by nearly one-half of the time during bone removal with the conventional method thereby reducing the kinking effect to the palatal pedicle and gives good perfusion to the anterior segment. Materials and Methods: This study was conducted at Karpaga Vinayaga Institute of Dental Sciences composing of 20 patients in which male: female ratio was 8:12, with a mean age of 25-30 years. This bird wing segment technique is performed following presurgical orthodontics under the guidance of clinical assessment of the gummy smile with an incisal show when the lip is at repose (vertical maxillary excess), especially for the calculated amount of superior repositioning. It is calculated by subtracting 2 mm from the total amount of an incisor show when the lip is at repose. The normal incisal show when the lip is at repose is 2 mm. After conventional primary AMO cut was performed, the precise calculated. Results: All our cases were tested positive for pulp vitality, no relapse, and minimal edema and with no changes in the bite or dentoalveolar relation followed until 1 year postoperatively indicating a good perfusion to the anterior segment and all the patients were satisfied esthetically and free of complaints. Conclusion: This simple technique allows the precise amount of calculated bone removal in a single piece from the nasal floor markedly reduces the duration of the surgery by nearly one-half of the time during bone removal with the conventional method there by reducing the kinking effect to the palatal pedicle and maintains good perfusion.